Manajemen Kelas dalam Kelas Bahasa Inggris: Studi Kasus Kelas Sebelas di SMA Negeri 2 Sigi: Integrasi Marzano dan Bronfenbrenner: Studi Berperspektif Ganda tentang Pengelolaan Kelas Bahasa Inggris sebagai Bahasa Asing di Sulawesi Tengah - Siti Lailatuz Zahro; Ruslin; Hijrah Syam; Nur Asmawati; Moh. Aditya Erlangga (Language Development Center, 2025)
Background: Classroom management in EFL setting is pivotal not only for maintaining order but also for fostering academic achievement and creating a positive learning environment. Purpose: This study employs qualitative a case study approach to examine classroom management practices within English as a Foreign Language (EFL) setting, focusing specifically on eleventh grade at SMAN 2 Sigi. Method: This qualitative case study collected data through semi-structured interviews with one EFL teacher and ten students, supplemented by document review, and data were analyzed using thematic analysis to identify key patterns in the data. Results and Discussion: The study reveal that both the EFL teacher and students demonstrates a shared positive understanding of classroom management. The EFL teacher implemented comprehensive the aspects of classroom management based on Marzono’s theory (2005), including rules and procedures, discipline and consequences, positive EFL teacher-students relationships, and awareness and flexibility in responding to classroom dynamics, which enhanced students comfort, engagement, and motivation. However, barriers such as low basics skill in English, emotional instability, inadequate facilities and curriculum implementation, and disruptive behaviors persisted, aligning with Bronfenbrenner’s theory (2005) on external influences affecting learning outcomes. This study addresses a gap in understanding local implementation of Marzono’s theory and is further integration of Bronfenbrenner’s theory in Indonesia EFL contexts. Conclusions and Implications: The implementation of classroom management in EFL setting, specifically in eleventh grade at SMAN 2 Sigi reveal that the EFL teacher applies classroom management in a structured, proactive, affective, and flexible, which enhances student engagement and positive classroom interactions. The findings emphasize the importance of the EFL teacher’s dedication, flexibility, and awareness in responding to the frequently changing classroom dynamics, while also providing a comprehensive understanding of classroom management practices, the integration of two theories, and the influence of social, cultural, and institutional factors on EFL learning.